Religious Values On Poems of Ziaroh 1 (Nilai Religi Pada Puisi Ziaroh 1) - Kodrat Eko Putro Setiawan (Indonesian Language Education and Literature, 2018)
This research aims to reveal the meaning of Riffaterre semiotic approach through heuristic reading, hermeneutic reading, matrix, model, variant, hypogram, and poetry relevance entitled Ziaroh 1 with Islamic teachings. The method used is a qualitative interpretive method with content analysis. The results of this study are: 1) in the heuristic reading, there are thirteen lines referentially meaning the words in the poem are derived from KBBI; 2) on hermeneutic readings, there are thirteen lines that have the meaning of an activity (pilgrimage) in remembrance of a deceased person, ie mother; 3) bermatriks, a child who misses his late mother; 4) modeled, poetic and all forms of action derived from the "I" attitude; 5) take a run, I'll take care of you; iron fences and tombs; it flowed water. The relevance to the teachings of Islam, namely the awareness of the certainty about death; surrender to God; and devoted to the elderly.Â Penelitian ini bertujuan mengungapkan makna dengan pendekatan semiotik Riffaterre melalui pembacaan heuristik, pembacaan hermeneutik, matriks, model, varian, hipogram, serta relevansi puisi berjudul Ziaroh 1 dengan ajaran Islam. Metode yang digunakan ialah metode kualitatif interpretatif dengan analisis konten. Hasil penelitian ini: 1) pada pembacaan heuristik, terdapat tiga belas baris yang secara referensial arti kata-kata dalam puisi tersebut berasal dari KBBI; 2) pada pembacaan hermeneutik, terdapat tiga belas baris yang memiliki makna sebuah kegiatan (ziarah) mengenang seseorang yang telah meninggal dunia, yaitu ibu; 3) bermatriks, seorang anak yang merindukan mendiang ibunya; 4) bermodel, puitis dan segala bentuk tindakan yang bersumber dari sikap â€œakuâ€; 5) bervarian, kukenang dirimu; pagar besi dan pusara; tetirah itu mengalir banyu. Adapun relevansi dengan ajaran Islam, yaitu kesadaran adanya kepastian tentang kematian; berserah diri kepada Allah; dan berbakti pada orang tua.